Customized antimicrobial efficacy tests offer superior evaluation of growth inhibitor efficacy for liquid microbial products. Issue 2 (February 2020) - Gorsuch, John P.; Jones, Zachary
Abstract: Antimicrobial effectiveness tests are common methods used to assess the risk of microbial contamination in pharmaceuticals and cosmetics. These assays may be inappropriate for endospore-based microbial products which often carry a similar – if not greater – risk of microbial contamination. In the present study, we compared the antimicrobial efficacy assessment provided by United States Pharmacopeia Chapter <51> Antimicrobial Effectiveness Testing with a modified test which utilized a customized bacterial challenge. The customized challenge inoculum comprised an assemblage of 12 bacterial strains (both pathogens and spoilage organisms) isolated from the product's end-use geography. Results suggest that some microbial inhibitor systems which pass industry standard antimicrobial effectiveness tests may fail when challenged with a customized bacterial assemblage. In order to provide the best possible assessment of microbial inhibitor systems for liquid Bacillus products, we suggest that new antimicrobial effectiveness tests be developed for this product class which include the addition of field-relevant contaminants in addition to the industry standard pathogen challenge. Abstract : Microbiology; Antimicrobial effectiveness test; Bacillus; Liquid microbial products; Bacterial contamination.